Ezekiel - Odell, Margaret S. (Smyth & Helwys Bible Commentary, 2017)
The book of Ezekiel reflects a degree of liteary coherence unmatched in the canon of biblical prophets. Organized around three major visions of God, the book tells the story of God's final attempt as their only legitimate king to claim the loyalty of his subjects, the rebellious and recalcitrant house of Israel. The prophet Ezekiel plays a key role in this campaign